Comparative evaluation of a family of isolated Ćuk DC/DC converter with step‐up techniques. Issue 16 (1st December 2020) - Faistel, Tiago Miguel Klein; Guisso, Ronaldo Antonio; Andrade, António Manuel Santos Spencer; da Silva Martins, Mário Lúcio
Abstract : In this study, a comparative evaluation of a family of isolated Ćuk DC/DC converter with step‐up techniques is presented. The voltage gain techniques are the reduced redundant power processing and the voltage multiplier. In addition, a detailed comparative analysis of the converters is showed. This comparison comprises features, such as the principle of operation, voltage gain curves, voltage and current stresses, design methodology, and estimated losses. By these comparisons, the main features and constraints of the analysed converters are identified. Four 200 W prototypes were constructed and evaluated in the laboratory. The isolated Ćuk converter with voltage multiplier showed the best performance and a peak efficiency of 95.86%.